Application of 2-D Vertically Averaged Boundary-Fitted Coordinate Model of Tidal Circulation in Thale Sap Songkhla, Thailand - PORNPINATEPONG, Somboon; TANAKA, Hitoshi; TAKASAKI, Mitsuru (Walailak Journal of Science and Technology (WJST), 2011)
A 2-D vertically averaged boundary-fitted coordinate hydrodynamic model was employed to simulate circulation in Thale Sap Songkhla due to tides in the Gulf of Thailand. The model was calibrated against a set of current velocity data collected between June and July 1997. The best fit for observations at Ko Yo and Pak Ro was achieved. To comprehend the hydrodynamic in the lake, the current vectors were illustrated for both the flood and ebb stages. Detailed analysis indicated that there existed a turning current at the northern tip of Ko Yo Island, which induced a significant current along its northern shoreline. The calculations show the current was stronger in the deep channel north of Ko Yo than in the southern circuit. The model also predicted a gyre near the deep channel of the lake entrance, which persisted for some time during the changing direction of the flood and ebb currents.